Adverse health events associated with clinical placement: A systematic review. (May 2019) - Graj, Ella; Sheen, Jade; Dudley, Amanda; Sutherland-Smith, Wendy
Abstract: Objective: Clinical placement is a fundamental aspect of student learning and skill development across healthcare disciplines. However, participation in clinical placements can also present significant risk to students. This systematic literature review sought to examine the range of risks and hazards encountered by students across healthcare disciplines during their clinical placements. Design: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis reporting guidelines were utilised in conducting this exploratory systematic review. Data sources: The CINAHL Complete, Medline Complete, and PsycINFO databases were searched. Reference lists of eligible records obtained via database searching were screened, and a supplementary key author search was conducted. Research published between 2013 and 2018 and conducted in the context of comparative international healthcare systems was the focus of this study. Review methods: Study titles and abstracts were screened, and the full text of potentially relevant records was perused. Records meeting key eligibility criteria by addressing risk posed to students in healthcare disciplines within a clinical placement context were included in the final synthesis. Results: The search identified 46 eligible records. The literature highlighted the worrying trend that students, most notably in the nursing discipline, can be exposed to a wide range of risks and adverse health events during clinical placement. Conclusions: As risks in unpredictable clinical environments cannot be eradicated, this review demonstrated a critical need for educative action to enable students to competently and confidently manage risks, and to reduce occurrence of adverse health events.